2005
DOI: 10.1111/j.1540-8167.2005.40764.x
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Tachycardia Induced by Biventricular Pacing in Patient with Severe Ischemic Cardiomyopathy

Abstract: This case represents a clear example of CRT induced proarrhythmia, which required inactivation of LV pacing for effective acute management. Such an intervention should be considered in CRT patients who exhibit a notable increase in drug refractory VT episodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 12 publications
2
47
0
1
Order By: Relevance
“…7 Although suppression of recurrent VT with catheter ablation has been reported, 7,8 treatment most often required inactivation of LV pacing, depriving these patients of the beneficial effects of resynchronization. 5,6 Prognosis is poor, even after control of recurrent VT, with a 50% mortality rate and frequent progression to refractory HF. 7 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7 Although suppression of recurrent VT with catheter ablation has been reported, 7,8 treatment most often required inactivation of LV pacing, depriving these patients of the beneficial effects of resynchronization. 5,6 Prognosis is poor, even after control of recurrent VT, with a 50% mortality rate and frequent progression to refractory HF. 7 …”
mentioning
confidence: 99%
“…3 Despite this, CRT-induced proarrhythmia has been reported as a clinically serious, rare, and unpredictable phenomenon. [4][5][6][7] Patients usually present with recurrent sustained ventricular tachycardia (VT)/electrical storm (ES), refractory to antiarrhythmic drugs, often accompanied with HF deterioration and cardiogenic shock. 7 Although suppression of recurrent VT with catheter ablation has been reported, 7,8 treatment most often required inactivation of LV pacing, depriving these patients of the beneficial effects of resynchronization.…”
mentioning
confidence: 99%
“…In several reported studies, monomorphic or polymorphic ventricular tachycardia (VT) was shown to be induced by BVP [18][19][20][21] , but in several other studies, CRT was shown to have an antiarrhythmic effect [22][23][24][25][26] . Experimental studies have shown that left ventricular epicardial pacing and BVP increase the QT and JT intervals and transmural dispersion of repolarization by altering the transmural sequence of activation of the intrinsically heterogeneous ventricular myocardium 7,8) .…”
Section: Discussionmentioning
confidence: 99%
“…[50][51][52] Paradoxically, there also has been several case reports of ventricular arrhythmia storm post cardiac resynchronization therapy, either de novo implants or upgrades. [53][54][55] The mechanism of arrhythmia storm has been speculated to be related to the heterogeneous transmural repolarization across the ventricle 56 and possible concealment related to left or bi-ventricular pacing. The programmed pacing from the left ventricular lead of the resynchronization device has been reported to reinitate reentrant ventricular tachyarrhythmias by concealment into a potential VT circuit antidromically setting up conditions allowing for propagation of the wavefront orthodromically within the VT circuit.…”
Section: Cardiac Resynchronization Therapy and Es Eventsmentioning
confidence: 99%